PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada PT Bank Syariah Mu’amalah Cilegon) - Rizal Zulkarnain; HER Taufik; Agus David Ramdansyah (Jurnal Manajemen dan Bisnis, 2020)
Competitive quality of products and services requires marketers to be able to provide some quality products and satisfactory service. This study was conducted to determine the effect of service quality and product quality on customer loyalty and customer satisfaction by taking samples of 93 customers Muamalah savings sampling technique. Research data in the analysis using SEM-PLS method. Based on the result of research shows that service quality has positive and significant effect to customer loyalty, product quality has positive and significant effect to customer loyalty, service quality has positive and significant effect to customer satisfaction, product quality has positive and significant impact to customer satisfaction, and customer satisfaction has positive effect significant to customer loyalty.